Determinantes da estrutura de capital das micro e pequenas empresas: uma abordagem comportamental - Cavalheiro, Everton Anger (2015)
The study of the capital structure is a subject that is considered by many as one of the high complexities. Several theories, based on the rationality paradigm, were created to explain the decisions about the funding sources' mix of the organizations; however, each theory seeks to present solutions to specific problems on this subject to great corporations. Nevertheless, despite its large contribution to the current economic system, the study on the determinants of the capital structure of micro and small companies is yet widely neglected. This research seeks to study these determinants from a complementary perspective to the traditional approach. We created and validated a model that can entail the variables that are traditionally connected to the companies performance (size, growth, profitability, and life cycle stage) together with the variable bound to the manager s relationships (number of products used), and also seed to associate such as variables to the personality traits of the manager-owner (optimism, overconfidence, sense of control and aversion to debt). In order to solve the research problem, a survey research is suggested with the entrepreneurs in Rio Grande do Sul. The sample to be selected will be of 625 micro and small entrepreneurs. Once the data was collected, all constructs were validated. By structural equation modeling was realized that the firm's performance was the main determinant of capital structure, in which the greatest growth, greatest profitability, the largest asset size and most advanced in the life cycle stage, implies on lesser organizational leverage. From this result, we conclude that to the extent that the company offers the opportunity to use internally generated funds, the entrepreneur tends to prefer them to finance the company's assets, to the detriment of external resources. In another hand, the banking service variable was positively associated with leverage. We conclude that the major number of banking services, used by the firm, contributes to decrease informational asymmetry, increasing access to credit, to the extent that the lender can form a better image of the company. In a complementary way, it was realized that the Managerial Traits has significant importance in decisions about capital structure, in that the positive expectations, the greater confidence of the entrepreneur, the negative attitude towards debt and the lesser locus of control (external) influence the capital structure, promoting as a result, the use of internal resources to the organization. It was also observed influence, though indirect, gender, since the female gender influenced negatively the performance of firms, and the lowest use of banking services.